Religion, science, and democracy a disputational friendship - Stenmark, Lisa L., 1961- (Lanham : Lexington Books, 2013)
This book uses Hannah Arendt's work to understand the paradoxical role of religion and science in public life and to develop a model for the science and religion discourse which does not focus on truth claims, but rather promotes public discourse and judgment. It advocates the position of the storyteller, who never tells a definitive story but instead seeks more stories, and promotes a disputational friendship in which we seek out points of disagreement in order to expand the conversation and incorporate more stories.
Introduction; Chapter One Religion, Science, and the "Culture Wars"; Chapter Two Science, Neutrality, and Public Life; Chapter Three Authority; Chapter Four The Art of Distinctions; Chapter Five Religion, Science, and Politics; Chapter Six Religion and Science as Social Activities; Chapter Seven Beyond Doctrines and Discoveries; Chapter Eight A Disputational Friendship; Bibliography
Includes bibliographical references and index.
Print version record.
Keywords: Religion and science; Culture conflict; Arendt, Hannah, -- 1906-1975.; RELIGION -- Religion & Science; Arendt, Hannah, -- 1906-1975; Culture conflict; Religion and science; Electronic books